More Than Gliding: Involvement of GldD and GldG in the Virulence of Flavobacterium psychrophilum - Pérez-Pascual, David; Rochat, Tatiana; Kerouault, Brigitte; Gómez, Esther; Neulat-Ripoll, Fabienne; Henry, Celine; Quillet, Edwige; Guijarro, Jose A.; Bernardet, Jean F.; Duchaud, Eric (Frontiers in Microbiology, 2017)
A fascinating characteristic of most members of the genus Flavobacterium is their ability to move over surfaces by gliding motility. Flavobacterium psychrophilum, an important pathogen of farmed salmonids worldwide, contains in its genome the nineteen gld and spr genes shown to be required for gliding or spreading in Flavobacterium johnsoniae; however, their relative role in its lifestyle remains unknown. In order to address this issue, two spreading deficient mutants were produced as part of a Tn4351 mutant library in F. psychrophilum strain THCO2-90. The transposons were inserted in gldD and gldG genes. While the wild-type strain is proficient in adhesion, biofilm formation and displays strong proteolytic activity, both mutants lost these characteristics. Extracellular proteome comparisons revealed important modifications for both mutants, with a significant reduction of the amounts of proteins likely transported through the outer membrane by the Type IX secretion system, indicating that GldD and GldG proteins are required for an effective activity of this system. In addition, a significant decrease in virulence was observed using rainbow trout bath and injection infection models. Our results reveal additional roles of gldD and gldG genes that are likely of importance for the F. psychrophilum lifestyle, including virulence.